2016
DOI: 10.2147/ott.s113909
|View full text |Cite
|
Sign up to set email alerts
|

Intravoxel incoherent motion model&ndash;based analysis of diffusion-weighted magnetic resonance imaging with 3 <em>b</em>-values for response assessment in locoregional therapy of hepatocellular carcinoma

Abstract: PurposeThe aim of this study was to evaluate an intravoxel incoherent motion (IVIM) model–based analysis of diffusion-weighted imaging (DWI) for assessing the response of hepatocellular carcinoma (HCC) to locoregional therapy.Patients and methodsRespiratory-gated DWI (b=0, 50, and 800 s/mm2) was retrospectively analyzed in 25 patients who underwent magnetic resonance imaging at 1.5 T before and 6 weeks following the first cycle of transarterial chemoembolization therapy, transarterial ethanol-lipiodol emboliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…This is in line with previous findings regarding tumor tissue characterization and therapy-response assessment [8,13], although contradicting results have been reported for prostate cancer [16]. The distribution of D and f was substantially altered by the treatments, suggesting a therapeutic effect on at least a subset of the studied tumors.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This is in line with previous findings regarding tumor tissue characterization and therapy-response assessment [8,13], although contradicting results have been reported for prostate cancer [16]. The distribution of D and f was substantially altered by the treatments, suggesting a therapeutic effect on at least a subset of the studied tumors.…”
Section: Discussionsupporting
confidence: 84%
“…has not yet been established and thus varies between studies [12,13], although some work has been done regarding optimization of three-b-value protocols [27,28]. However, as long as the chosen model is valid for the particular b values, choice of b values should only have minor effects on the observed estimation trends.…”
Section: Consensus Regarding B Values For Estimating Ivim D and Fmentioning
confidence: 99%
See 1 more Smart Citation
“…In the presented 3.0 T study, in addition to b-values of 0 and 1000 s/mm2, a low b-value of 50s/mm 2 was included in the sequence for a rough assessment of perfusion effects. From the used three b-values it is possible to obtain perfusion sensitive biomarkers as ADC(0, 50) [34] , estimation of perfusion fraction [35][36][37][38][39][40] or simply the ADC Diffusion-Weighted Whole-Body MRI difference between the conventionally used ADC(0,1000) and the ADC(50, 1000), which is less affected by perfusion effects, as in the present study. With this simplified IVIM approach, a further separation into perfusion fraction and pseudodiffusion coefficient as obtained for full IVIM approaches is not possible.…”
Section: Discussionmentioning
confidence: 79%
“…Woo et al [107] and Mürtz et al [108] found a significant correlation between IVIM-derived parameter (fp) and percent of arterial enhancement whether in the initial diagnosis of HCC or after the locoregional therapy. Hence, it could be used after locoregional therapy to distinguish responders from non-responders especially if there is contraindication for contrast administration (Fig.…”
Section: Mri Appearance After Locoregional Treatmentmentioning
confidence: 99%